2020
DOI: 10.1001/jamanetworkopen.2020.6445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Person Navigation to Address Family Social Needs on Child Health Care Utilization

Abstract: IMPORTANCE While many organizations endorse screening for social risk factors in clinical settings, few studies have examined the health and utilization effects of interventions to address social needs. OBJECTIVE To compare the acute care utilization effects of a written resources handout vs an in-person navigation service intervention to address social needs. DESIGN, SETTINGS, AND PARTICIPANTS In this secondary analysis of a randomized clinical trial, 1809 adult caregivers of pediatric patients seen in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 13 publications
(18 reference statements)
2
65
2
Order By: Relevance
“…To describe the structure of workforce models performing these activities, studies were first sorted by mode of administration used for screening. We found 37 studies used self-administered screening with patients, 29,30,32,34,41,42-46,48,52-54,56,59,61,62,64-66, 68,69,71-73,75-77,79,80-84,86,87 24 studies used clinician-administered screening, [26][27][28]31,33,[35][36][37][38][39][40]47,[49][50][51]57,60,63,74,78,85,[88][89][90] 3 studies used both, 55,58,70 and 1 study did not mention the mode screening administration 67 (Figure 2). We then categorized the workforce associated with each screening administration type and the roles who responded to identified needs.…”
Section: Workforce Modelsmentioning
confidence: 93%
See 4 more Smart Citations
“…To describe the structure of workforce models performing these activities, studies were first sorted by mode of administration used for screening. We found 37 studies used self-administered screening with patients, 29,30,32,34,41,42-46,48,52-54,56,59,61,62,64-66, 68,69,71-73,75-77,79,80-84,86,87 24 studies used clinician-administered screening, [26][27][28]31,33,[35][36][37][38][39][40]47,[49][50][51]57,60,63,74,78,85,[88][89][90] 3 studies used both, 55,58,70 and 1 study did not mention the mode screening administration 67 (Figure 2). We then categorized the workforce associated with each screening administration type and the roles who responded to identified needs.…”
Section: Workforce Modelsmentioning
confidence: 93%
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 3 more Smart Citations